A Review on Pramehahara Dravya of RajaNighantu - Verma, Priyanka; Soni, Pradeep (International Research Journal of Ayurveda & Yoga, 2024)
Background: Nighantus plays an important role in Ayurveda as they give knowledge about herbo-mineral drugs and describe their properties in easy manner. There are many drugs described in Brihatrayee and Laghutrayee which show Pramehahara effects. After Samhita period, many Nighantus came. RajaNighantu as per name is the raja of all Nighantus. There are 23 Varga’s in RajaNighantu. Prameha is the Santarpana Janya Vyadhi. Twenty types of Prameha are described in Charaka Samhita, which includes 10 types of Kaphaj Prameha, six types of Pittaj Prameha, and four types of Vataj Prameha. Diabetes mellitus can correlate with Madhumeha, which is a type of Vataj Prameha. Purpose: This study’s goal is to compile a list of RajaNighantu’s beneficial herbs for Prameha/DM. Materials and Methods: Journals, the internet, and other appropriate ayurvedic and modern literatures were used in addition to RajaNighantu to gather knowledge on the subject. Results and Discussion: RajaNighantu described 51 dravyas for the treatment of Prameha. Among them 37 Audbhida dravya, seven Parthiva dravya, and four Jangam dravya as Pramehahara. Apart from these, Shritasita jala, Puranaguda, and Madhavi madya are also described as Pramehahara. According to the Rasa, 15 had Madhur rasa, 13 had Tikta rasa, seven had Katu rasa, four had Kashaya rasa, one had Amla rasa, and one had Lavan rasa, respectively. Diabetes mellitus (DM) describes a collection of related metabolic disorders that are characterized by hyperglycemia. Genetics and environmental factors combine intricately to generate multiple kinds of DM. Reduced insulin secretion, decreased glucose utilization, and increased glucose production are some of the factors that contribute to hyperglycemia, depending on the etiology of the diabetes. The metabolic dysregulation linked to DM results in secondary pathophysiologic alterations in various organ systems, which significantly impact both the diabetic patient and the health-care system.[1] India is becoming the global hub for diabetes due to the rising prevalence of this illness.